2017
DOI: 10.1253/circj.cj-17-0438
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Over Trial of Febuxostat and Topiroxostat for Hyperuricemia With Cardiovascular Disease (TROFEO Trial)

Abstract: to reduce UA more potently than allopurinol, 7 while topiroxostat has a similar effect to allopurinol. 8 No study, however, has compared febuxostat with topiroxostat. Accordingly, a clinical study was conducted to compare febuxostat with topiroxostat and assess potential differences in efficacy (TopiROxostat and FEbuxostat in a randomized, Open-label, cross-over trial for hyperuricemia with cardiovascular disease (TROFEO trial). Methods Study ProtocolThe subjects were outpatients with cardiovascular disease an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…To‐date, the effects of UA‐lowering drugs on blood lipids remain inconclusive. In animal experiments and clinical studies, conflicting data have been reported . Despite the negative results in Sezai's study, we can see a declining trend in the numerical value of triglycerides after 1 month when patients were treated with febuxostat .…”
Section: Discussionmentioning
confidence: 55%
“…To‐date, the effects of UA‐lowering drugs on blood lipids remain inconclusive. In animal experiments and clinical studies, conflicting data have been reported . Despite the negative results in Sezai's study, we can see a declining trend in the numerical value of triglycerides after 1 month when patients were treated with febuxostat .…”
Section: Discussionmentioning
confidence: 55%
“…In a previous study, it showed tolerability and non‐inferior SUA‐lowering effect to allopurinol in hyperuricemic patients with or without gout . Furthermore, topiroxostat and febuxostat showed similar renal protective and anti‐inflammatory effects after 6‐month treatment in hyperuricemic patients with cardiovascular disease . In recent years, the organ protective effect of these novel XOR inhibitors has been suggested, which has gained considerable attention.…”
Section: Introductionmentioning
confidence: 95%
“…The study result demonstrated that febuxostat caused greater and more rapid reduction of s-UA than topiroxostat, as well as an antioxidant effect superior to topiroxostat. 9) However, that study did not compare the two drugs in patients with CKD, so we performed a sub-analysis of CKD patients from the TROFEO trial in the present study (TROFEO CKD trial). All patients in TROFEO trial were those who underwent cardiovascular surgery.…”
Section: Introductionmentioning
confidence: 99%